Integration of Islamic Boarding School Culture and Project-Based Learning in Strengthening Islamic Character Education for Modern Curriculum - Arif Efendi; Moh. Zainudin (SKYHAWK : Jurnal Aviasi Indonesia, 2026)
This study examined the integration of pesantren cultural values with Project-Based Learning (PjBL) in strengthening Islamic character education in higher education. A qualitative approach was employed involving 20 undergraduate nursing students at Universitas Bina Sehat PPNI Mojokerto selected through purposive sampling. Data were collected through semi-structured interviews, observations, and documentation, then analyzed using thematic procedures including data reduction, categorization, and verification. The findings indicate that integrating pesantren culture with PjBL effectively strengthens discipline, responsibility, cooperation, respect, spirituality, and moral awareness through authentic and collaborative learning experiences. Students also demonstrated improved learning independence, critical thinking, and process-oriented learning attitudes. However, challenges related to passive learning habits, adaptation to collaborative learning, and unequal participation were still identified. The study further reveals that lecturer facilitation and institutional support significantly influence implementation effectiveness. Theoretically, this study contributes to culturally responsive and holistic education frameworks by integrating religious-cultural values into contemporary project-based learning.